Effect of simulated purse seine fishing on acclimated sardines and post-fishing interactions with predators - Marçalo, A. (2016)
The fate of fish deliberately released (slipped) during purse seining is poorly studied and estimating unaccounted mortality rates in pelagic fisheries has been difficult and imprecise.